Optimalisasi Sistem Enterprise Resource Planning Menggunakan Modul Inventory pada UMKM Studi Kasus JAPFA BEST Serpong - Luarwan, RyanReynaldy; Reynaldy Ryan Luarwan; Aprilia, Windy; Hajar, Dewi (Multmedia Nusantara Politeknik, 2025)
The food and beverage industry in Indonesia is experiencing significant growth, and Japfa Best Serpong as part of Japfa Comfeed Indonesia Tbk. faces operational challenges related to product quality management, particularly in inventory management and product delivery. This research aims to analyze and optimize the implementation of ERP system, especially Odoo inventory module, to improve the efficiency of inventory management and reduce stock recording errors. The research methodology was conducted through interviews with the Administrator of Japfa Best Serpong, analysis using Porter's Value Chain Model, and design and testing of an Odoo-based ERP system. The results show that the implementation of the Odoo inventory module can increase the accuracy of stock records, improve product quality control, and reduce losses due to customer complaints and refunds. The system also enables better integration with logistics partners and flexibility in feature customization, which supports continuous innovation for the company. In conclusion, implementing Odoo as an ERP solution can increase Japfa Best Serpong's competitiveness in an increasingly competitive industry by improving operational efficiency and customer service quality.